SURVEI MANAJEMEN SUPORTER MACAN MURIA KUDUS (SMM) DALAM MENINGKATKAN PRESTASI PERSIKU KUDUS (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the management of the Muria Kudus Macan Supporters (SMM) in improving the performance of Persiku Kudus. This research is qualitative research. The location of this research was conducted at the secretariat office of the Macan Muria Supporters (SMM) Gor Bung Karno Kudus shophouse. The research objectives of this study were coaches, general chair, daily chair and supporting member of football. The research instruments used are observation, interviews, and documentation. Triangulation method is used to check the validity of the data. Data analysis uses data reduction, data display, and data conclusion drawing / verification. The results of the study showed that, 1) The planning carried out by the management of the Muria Kudus Tigers Supporters in improving the performance of the Persiku team went quite well. With the vision and mission of the management will make the Muria Tiger Supporters can determine the direction and goals to be achieved. In addition, planning for internal activities is also well structured. 2) The organizing carried out by the management of the Muria Tigers Supporters went well. Evidenced by the reorganization once every 3 years, the management of the Muria Tiger Supporters will not die and keep going. 3) The movement carried out by the Muria Tiger Supporters to improve the performance of Persiku has gone well. In every Persiku match both at home and away matches, Supporters of the Muria Kudus Tigers are always moving and compact to provide support to Persiku Kudus. 4) Supervision carried out by the management of Muria Tiger Supporters to advance the performance of Persiku went well. Supervision is carried out continuously and continuously starting from supervision during the competition, monitoring the performance of the board, and supervision of the members of the Muria Tigers Supporters. The conclusion in this study is the management of the Holy Muria Holy Supporters (SMM) in improving the performance of Holy Persiku has been going well.